Estimating the useful life of the sempor reservoir using erosion modelling - Budiman, Satrio; Suprayogi, Slamet (Quaestiones Geographicae, 2024)
Sedimentation determines how optimal a reservoir functions throughout its design life. The Sempor Reservoir in Central Java, Indonesia, will be 45 years old in 2023. At least 15 million m3 of particles have been sedimented in the reservoir for >30 years, reducing its function as an irrigation water source to only 60%. Therefore, assessing its performance in providing irrigation water and generating hydropower electricity is essential, given that its design life ends in 2028. This study was conducted to analyse the sedimentation and estimate the useful life of the Sempor Reservoir based on the erosion potential in its catchment area. The potential sedimentation rate was formulated from erosion potential assessed using the universal soil loss equation (USLE) model, sediment delivery ratio (SDR) and trap efficiency (TE). By contrast, the actual sedimentation rate was determined from changes in the dead storage capacity from 2013 to 2023. The interpolation performance evaluation of the bathymetric survey results was tested using the coefficient of determination (R2), Nash-Sutcliffe efficiency (NSE), and mean absolute percentage error (MAPE) which resulted in values of 0.917; 0.87; and 13.03%, respectively. The results show that the catchment area had an erosion potential of 3,405,353.86 t∙a−1, resulting in a potential sedimentation rate of 309,106.63 m3∙a−1. The calculated actual sedimentation rate was 33,903.28 m3∙a−1. Therefore, the useful life of the Sempor Reservoir was estimated to end in 0.5 years and 4.59 years based on the potential and actual sedimentation rates, respectively.